Parametric Study of Active Solar Heating Using a Pebble Bed as a Thermal Collector and Storage Unit (Journal of Engineering, 2014)
In this study, pebble bed as an absorber and storage material was placed in a south facing, flat plate air-type solar collector at fixed tilt angle of (45°). The effect of this material and differ- ent parameters on collector efficiency has been investigated experimentally and theoretically. Two operation modes were employed to study the performance of the solar air heater. An inte- grated mode of continuous operation of the system during the period of (11:00 am – 3:00 pm) and non-integrated mode in which the system stored the solar energy through the day then used the stored energy during the period of (3:00 pm – 8:00 pm). The results of parametric study in case of continuous operating showed that the maximum average temperature difference of air between inlet and outlet sections observed on (0.018 kg/s) air mass flow rate were exceeded (17°C) and the maximum outlet temperature that got was exceeded (34°C) for the three months (December, January and February) of experiments. Average efficiency was ranged from 53% to 65%. In the case of storage and then operating, the maximum outlet air temperature was ranged from (27°C) up to (31°C) then decreased with spend of energy to reach (13°C) to (18°C) and the maximum storage energy was (165.14 W) for the porosity of (0.29) , height of (20 cm) and (0.01 kg/s) mass flow rate. The results also, showed that the solar air collector supplied a solar heating fraction (SHF) with an average of (0.65) for a meeting room (3 * 4 * 7 m) located in Baghdad as a case study.